The influence of policy instruments on manufacturing Direct Foreign investment in developing countries - Root, Franklin R.; Ahmed, Ahmed A. (Journal of International Business Studies, 1978)
Forty-four economic, social, political and policy variables are tested for their significance in discriminating among three groups of developing countries designated “unattractive,” “moderately attractive,” and “highly attractive” with respect to foreign investment in manufacturing. Among the six essential discriminators, the only policy variable to emerge is the corporate tax level.